READING RATE AND FLUENCY BASED INSTRUCTION FOR CHILDREN WITH INTELLECTUAL DISABILITY: A CASE STUDIES - Fabiola CASARINI; Adele CARPITELLI (Studia Universitatis Babes-Bolyai, 2015)
We studied the effects of word fluency training on text reading rate in four students diagnosed with intellectual disability, from mild to severe. Prior and after the intervention, participants read three different texts for the age-graded level, to evaluate the effects of training on reading fluency. The independent variable was a fluency training for reading words based on Precision Teaching. During the intervention correct responses and faster rate of responding were reinforced. The results showed a significant improvement in oral text reading for all participants. Word fluency training seemed to be also efficient, requiring a brief intervention to reach important reading goals. ZUSAMMENFASUNG. Wir haben die wirkung eines training von einfluss lessen von einen textin vier schuler mit einer diagnose von mittlere und schwere intellektuelle behinderung studiert. Vor und nach dem eingreif sind an den schuler drei verchindene texten unterbreitet worden, zum die auswirkung. Bewerten von dem training des fliessenden lessen eines textes. Werent dem eingreif sind fliessende und richtige antworten belohnt worden. Die ergebnise zeigen ein bedeutende verbesserung im lessen bei allen scheint wirksam. Ein kurzer eingreif hat ermoeglicht das man nein wichtiges ziel erreicht hat. Das lessen, das fliessende lessen genauigkeit teaching, behinderung lessen training einfluss woerter fliessende ziele, leistung, wirksamkeit. Schlusselworter: Mundelselsefluss, Praezisioni lehre, Behinderung, Unterricht fliessend, Effectiveness, Wirkungs.